Effects of Physical Education Learning Management in Track Applying Cippa Model Principle with Motivation Theory on Physical Fitness, Skills, and Attitude for Healthy Running of Lower Secondary School Students - Rukkatiwong, Tawatchai; Chalapirom, Bancha; Samawathdana, Rungrawee (Journal of Education Studies, Chulalongkorn University, 2020)
This research aimed to study the effects of physical education learning management in track applying Cippa model principle with motivation theory on physical fitness, skills, and attitude for healthy running of lower secondary school students. Samples included 90 students from the eighth grade of Wittayanukulnaree School in Phetchabun. Forty-four students were assigned to the experimental group to study under the physical education learning management in track applying Cippa model principle with motivation theory while the other 46 students in the control group were assigned to study with conventional teaching methods. Researcher developed eight learning activity plans. The data were analyzed by using mean, standard deviation, and t-test. The research findings were as follows: 1) The mean scores of the physical fitness, skills and attitude for healthy running of the experimental group students after learning were significantly higher than before learning at a .05 level. 2) The mean scores of the physical fitness, skills and attitude for healthy running of the experimental group after learning were significantly higher than the control at a .05 level.